Stability analysis of non-thermal fixed points in longitudinally expanding kinetic theory - Mikheev, Aleksandr N.; Mazeliauskas, Aleksas; Berges, Jürgen (Arxiv, 2022)
We use the Hamiltonian formulation of kinetic theory to perform a stability analysis of non-thermal fixed points in a non-Abelian plasma. We construct a perturbative expansion of the Fokker-Planck collision kernel in an adiabatic approximation and show that the (next-to-)leading order solutions reproduce the known non-thermal fixed point scaling exponents. Working at next-to-leading order, we derive the stability equations for scaling exponents and find the relaxation rate to the non-thermal fixed point. This approach provides the basis for an understanding of the prescaling phenomena observed in QCD kinetic theory and non-relativistic Bose gas systems.
Gesehen am 20.09.2022